Lectotypification of Warszewiczia pulcherrima (Rubiaceae) with notes on Józef Warszewicz’s plant collection preserved at KRA herbarium from his trips to Central and South America - Nobis, Marcin; Głuszak, Tomasz; Zemanek, Alicja; Zemanek, Bogdan (Phytotaxa, 2020)
Warszewiczia Klotzsch (1853: 497) is a Neotropical genus of the tribe Condamineeae (Rova et al. 2002, Duncan 2007, Bremer & Eriksson 2009, Kainulainen et al. 2010, Delprete 2019), family Rubiaceae. The genus comprises seven well-distinguished species (Pantoja 1994, Tropicos 1995+) distributed in southern Central America and northern South America (Pantoja 1994, Lorence 1999, Kainulainen et al. 2010, Baksh-Comeau et al. 2016).